2010
DOI: 10.1039/b917619e
|View full text |Cite
|
Sign up to set email alerts
|

Host–guest interactions in azafullerene (C59N)-single-wall carbon nanotube (SWCNT) peapod hybrid structures

Abstract: The effect of azafullerene encapsulation on the electronic states of single-wall carbon nanotubes (SWCNTs) is investigated; UV-vis-NIR absorption and photoluminescence spectroscopy shows that the interaction between SWCNTs and the encapsulated azafullerenes is originated from the weak intermolecular forces, which suggests a lack of strong doping effect such as electron transfer between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…Spectroscopic characterization of azafullerene peapods has also been performed using a sample that was synthesized by vapor-phase filling methods. 13 The results suggest that azafullerene peapods may show p-type FET behavior similar to that of C 60 peapods. It was concluded that the discrepancy between these two reports may be caused by the different methods used to prepare the azafullerene materials.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…Spectroscopic characterization of azafullerene peapods has also been performed using a sample that was synthesized by vapor-phase filling methods. 13 The results suggest that azafullerene peapods may show p-type FET behavior similar to that of C 60 peapods. It was concluded that the discrepancy between these two reports may be caused by the different methods used to prepare the azafullerene materials.…”
mentioning
confidence: 60%
“…Our previous study revealed that a large portion of encapsulated C 59 N tends to form dimers. 13 However, we also observed that isolated C 59 N monomers are stable in SWCNTs. By counting the number of molecules of encapsulated C 59 N, it was found that 84% of C 59 N exists in a dimeric form, while 14% remains in an isolated monomers.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…The wavelength converted from the exited energy levels were estimated to be 1703 nm and 1061 nm, which were closed to experimental results of C 59 N-SWCNT by UV-vis NIR spectra and 2D PL contour maps as shown in Fig. 16 (a) (Iizumi, et. al.…”
Section: Electronic Structure Of N@c 60mentioning
confidence: 99%